Bifunctional Ag@SiO2/Au Nanoparticles for Probing Sequential Catalytic Reactions by Surface‐Enhanced Raman Spectroscopy. Issue 4 (22nd February 2017) - Wu, Yiren; Su, Dong; Qin, Dong
Abstract: We report the synthesis of bifunctional Ag@SiO2 /Au nanoparticles with an "islands in the sea" configuration by titrating HAuCl4 solution into an aqueous suspension of Ag@SiO2 core–shell nanocubes in the presence of NaOH, ascorbic acid, and poly(vinyl pyrrolidone) at pH 11.9. The NaOH plays an essential role in generating small pores in the SiO2 shell in situ, followed by the epitaxial deposition of Au from the Ag surface through the pores, leading to the formation of Au islands (6–12 nm in size) immersed in a SiO2 sea. By controlling the amount of HAuCl4 titrated into the reaction system, the Au islands can be made to pass through and protrude from the SiO2 shell, embracing catalytic activity toward the reduction of 4‐nitrophenol to 4‐aminophenol by NaBH4 . While the Ag in the core provides a strong surface‐enhanced Raman scattering activity, the SiO2 sea helps maintain the Au component as compact, isolated, and stabilized islands. The Ag@SiO2 /Au nanoparticles can serve as a bifunctional probe to monitor the stepwise Au‐catalyzed reduction of 4‐nitrothiophenol to 4‐aminothiophenol by NaBH4 and Ag‐catalyzed oxidation of 4‐aminothiophenol to trans ‐4, 4′‐dimercaptoazobenzene by the O2 from air in the same reaction system. Abstract : Islands in the sea : Bifunctional Ag@SiO2 /Au nanoparticles were used as a SERS probe to monitor the stepwise Au‐catalyzed reduction and Ag‐catalyzed oxidation reactions.